Japan’s arctic policy - Dmitry V. Streltsov (Сравнительная политика)
Abstract: The article is devoted to the public policy of modern Japan in the Arctic. The Japanese government has put forward clear and well-specifi ed targets of the intensifi cation of Japan’s efforts in the economic development of the Arctic region. Among the priorities of the Arctic policy one should mention such areas as the development of maritime transportation, development of hydrocarbon deposits of the Arctic shelf, sea fi shing, as well as the preservation and increase of the sea bioresources.